Formação do leitor : um bicho de quantas cabeças? - Vinco, Sônia Regina (2008)
This research investigates some aspects of the work of readers formation developed at Pedro II-RJ school, São Cristóvão Unit. From the notion that knowledge is woven in networks, it considers the relations between the experiences lived at school around the literary reading and the formation of students as readers. This school s first segment has 21 years of existence. Literature classes are included in its programme from the initial until the fourth grade. These classes existence is the result of a collective process of curriculum elaboration, which began in 1984. In this way, through the memories of teachers and some students who, nowadays, in its majority, course high school, the research penetrates into the scholarly daily life, intending to broaden the comprehension about the collective processes lived and its implication on the students subjectivities networks. Searching, in the interviews, to collect information that indicates if the reading work done at school constituted to these subjects a formation experience, the research presents elements that may help the reflections on the teaching staff practice.